Potential Bacterial Symbion of Sea Urchin As a Multi-Drug Resistant (MDR) Antibacterial Agent Against Staphylococcus aureus and Escherichia Coli Bacteria - Suzana Kristy Satriani Fofied; Agus Sabdono; Diah Permata Wijayanti (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
Staphylococcus aureus and Escherichia coli are pathogenic bacteria agent of many human diseases. Those bacteria infect in various levels and also been antibiotic resistants. Bacterial resistance has become a serious global problem. The purposes of this study were to isolate and identify the symbiotic bacteria of the Sea Urchin that have an antibacterial activity of the Strain Multi-Drug Resistant (MDR) against Staphylococcus aureus and Escherichia coli. Sea Urchin was taken from Panjang island, Jepara Indonesia at 2-3 m depth. The symbiotic bacteria were isolated from Sea Urchin by using dilution method and spread plate method. Phenotypic characteristics was observed on colony shape, color and texture of growing bacteria. While the streak method was used to purify bacterial symbion. The antibacterial activity test was performed using overlay method. The results showed that 3 out of 37 isolates have antibacterial activity against Staphylococcus aureus and Escherichia coli. The BB.03.35 isolate was selected for molecular identification due to the largest inhibitory zone diameter. The sequence of this bacterium showed 97% homology and closely related to Pseudoalteromonas flavipulchra.